2017
DOI: 10.1002/hipo.22768
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol rapidly increases GluA2‐mushroom spines and decreases GluA2‐filopodia spines in hippocampus CA1

Abstract: Hippocampal dendritic spine density rapidly increases following estradiol (E2) treatment, but the types of spines and trafficking of synaptic markers have received little investigation. We assessed rapid effects of E2 over time on the density of four spine types (stubby, filopodial, long thin and mushroom) and trafficking of AMPA receptor subunit GluA2 and PSD95 on tertiary, apical dendrites in CA1. Castrated male rats received 20 μg/kg of E2 or vehicle and were sacrificed 30 or 120 min later. Images of Golgi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
3
27
1
Order By: Relevance
“…The important attribute of post training protocols is that enhancements after immediate, but not delayed, post-trial injections show that the enhancing effects on memory do not derive from non-mnemonic effects such as psychological performance variables or learning since the treatments are given after the learning trial. Several labs, using post-training injections in recognition memory tasks, found that E 2 enhances consolidation of memory in OVX rodents when given immediately following T1 but not when given between 45 min to 2 h after T1 (Avila et al, 2017; Fernandez et al, 2008; Inagaki et al, 2012; Inagaki et al, 2010; Jacome et al, 2010; Lewis et al, 2008; Luine et al, 2003; Packard, 1998). The length of time required for memory consolidation varied depending on the dose of E 2 and the inter-trial delay between T1 and T2.…”
Section: Post Training Trial Injections Rapidly Enhance Memory Consolmentioning
confidence: 99%
See 4 more Smart Citations
“…The important attribute of post training protocols is that enhancements after immediate, but not delayed, post-trial injections show that the enhancing effects on memory do not derive from non-mnemonic effects such as psychological performance variables or learning since the treatments are given after the learning trial. Several labs, using post-training injections in recognition memory tasks, found that E 2 enhances consolidation of memory in OVX rodents when given immediately following T1 but not when given between 45 min to 2 h after T1 (Avila et al, 2017; Fernandez et al, 2008; Inagaki et al, 2012; Inagaki et al, 2010; Jacome et al, 2010; Lewis et al, 2008; Luine et al, 2003; Packard, 1998). The length of time required for memory consolidation varied depending on the dose of E 2 and the inter-trial delay between T1 and T2.…”
Section: Post Training Trial Injections Rapidly Enhance Memory Consolmentioning
confidence: 99%
“…Micevych’s group has shown that the ability of E 2 to rapidly activate lordosis and increase dendritic spines in the arcuate nucleus is directly linked to mGluR1 receptors (Micevych and Christensen, 2012). Associations of mERs with ionotrophic glutamate receptors (iGluRs) have also been identified: AMPA receptors GluR1 in the prefrontal cortex (Khan et al, 2013), GluR2 in hippocampus (Avila et al, 2017) and NMDA receptors NR1 in cortex (Sellers et al, 2015a) and NR2 in the hippocampus have all been shown to be activated by mERs. Most of these associations with NMDA receptors have been tied to modulation of spine density, memory formation or other behaviors rapidly modulated by estrogens, but further studies are required to establish the connections.…”
Section: Estrogen Induced Spinogenesis In Ca1: Potential Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations